The role of stretching in rehabilitation of hamstring injuries: 80 athletes follow-up - Malliaropoulos, N.; Papalexandris, S.; Papalada, A.; Papacostas, E. (Medicine & Science in Sports & Exercise, 2004)
For years, stretching has been an integral part of fitness, practice, and rehabilitation programs to decrease muscle stiffness and relieve pain associated with it. The increased joint range of motion (ROM), indicating the degree of muscle flexibility, has a benefit of stretching proven for healthy tissues. PURPOSE: The objective of our study was the assessment of the effects of stretching in the rehabilitation of hamstring injuries. METHODS: We followed up 80 Greek athletes, of average age 20.5 yr, with "second-degree" strain of the hamstring muscles. The athletes were divided into two groups, A and B. For both groups, we estimated the time required for the rehabilitation of the decreased knee ROM and the total time before the athletes could return to a full training program. RESULTS: Group B, which carried out a more intensive stretching program, was found to have a statistically significant shorter time of regaining normal ROM (5.57 +/- 0.71 d) and rehabilitation period (13.27 +/- 0.71 d) in comparison with group A (7.32 +/- 0.525 d and 15.05 +/- 0.81 d, respectively). CONCLUSION: Our results suggest that stretching is of great importance in treating muscle strain injuries in that it improves the effectiveness of the rest rehabilitation program.